Distribution and imaging characteristics of spina bifida occulta in young people with low back pain: a retrospective cross-sectional study - Wenhao Li; Zhencheng Xiong; Chunke Dong; Jipeng Song; Liubo Zhang; Jun Zhou; Yanlei Wang; Ping Yi; Feng Yang; Xiangsheng Tang; Mingsheng Tan (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Purpose Spina bifida occulta (SBO) is one of the most common congenital spinal deformities. Although many studies have demonstrated the influence of lumbosacral dysplasia on low back pain (LBP) in young athletes, there have been few studies on SBO among young people in other occupations. The purpose of this study is to investigate the distribution of SBO in young people with LBP and to classify SBO from the perspective of lamina development. Methods The X-ray films of 148 young patients with LBP were analyzed to quantify the distribution of SBO and classify abnormal laminae. Results Of the 148 patients, 93 (61.49%) had SBO: 83 cases involved S1 alone, 2 involved L5–S1, 5 involved S1–2, 2 involved S1–4, and 1 involved L4–S4. According to the degree of the defect, the patients with SBO were divided on the basis of five grades: 9 patients with grade I, 53 with grade II, 23 with grade III, and 8 with grade IV. The cases were classified by the shape of the laminae into 4 types: 15 cases of type a, 11 cases of type b, 37 cases of type c, and 30 cases of type d. Conclusion Among the young people with LBP that we surveyed, SBO is the most common lumbosacral dysplasia, which frequently involves the S1 segment. Most laminae in SBO are in the developmental stage of the spinous process, and an abnormal laminar growth direction and laminar stenosis are the most common laminar morphologies in SBO.